2016
DOI: 10.1177/0886260515624213
|View full text |Cite
|
Sign up to set email alerts
|

Kinship and Intimate Partner Violence Against Married Women in Ghana: A Qualitative Exploration

Abstract: In African societies, kinship ties determine how women are socialized, their access to power and wealth, as well as custody of children, often considered important factors in married women's experience of intimate partner violence (IPV). Yet studies that examine how kinship norms influence IPV are scant. Using in-depth interviews collected from women identifying with both matrilineal and patrilineal descent systems, we explored differences in Ghanaian women's experiences of IPV in both kin groups. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 56 publications
8
56
1
1
Order By: Relevance
“…Violence against women is widespread due to the socially accepted superior status of men and their right to assert power over females (Amoakohene, 2004). Cultural norms support male dominance and violence against women, this includes both intimate partner aggression and sexual harassment (Ardayfio-Schandorf, 2005;Aryeetey, 2004;Sedziafa, Tenkorang, & Owusu, 2016). Ghanaian women have reported victimization from emotional aggression (i.e.…”
Section: The Context Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Violence against women is widespread due to the socially accepted superior status of men and their right to assert power over females (Amoakohene, 2004). Cultural norms support male dominance and violence against women, this includes both intimate partner aggression and sexual harassment (Ardayfio-Schandorf, 2005;Aryeetey, 2004;Sedziafa, Tenkorang, & Owusu, 2016). Ghanaian women have reported victimization from emotional aggression (i.e.…”
Section: The Context Of the Studymentioning
confidence: 99%
“…Ghanaian women have reported victimization from emotional aggression (i.e. name-calling, accusations of witchcraft, stalking, husband's extramarital affairs) physical aggression (hitting, slapping, kicking, pushing, and beating), and sexual aggression (forced sexual intercourse and rape) by their husbands (Sedziafa et al, 2016).…”
Section: The Context Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This is exemplified in studies demonstrating that women who live with their matrilineal kin have higher fertility than women who do not and that women who live with their mothers are less likely to get divorced than those who live patrilocally (Leonetti et al, ; Sear, Mace, & McGregor, ). Furthermore, intimate partner violence is more often experienced by women in patrilineal and patrilocal societies (Sedziafa, Tenkorang, & Owusu, , ), and as a result, sexual conflict and household dissonance may increase the woman's stress load, thus worsening a woman's menopausal transition. The positive effect of a relaxed environment on menopause symptoms is highlighted by the fact mindfulness and meditation are now being recommended by practitioners as a natural method of treatment (Wong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, in Ghana, a mixed methods nationally representative study found that 44% of women who had experienced domestic physical violence in the previous 12 months had been ill in the 30 days prior to the survey, compared to 31% of women who had not experienced this type of domestic violence [4]. In studies in northern Ghana, women reported feelings of worthlessness, suicidal ideation, hypertension, sleep disruption, genital sores, and premature termination of pregnancy as a result of the violence they experienced [12,13]. The GFLHS study also identified strong correlations between exposure to IPV and serious mental illness.…”
Section: Literature/state Of Knowledgementioning
confidence: 99%